Exploiting self-tuning tristable to improve energy capture from shape memory oscillator. (July 2022) - Jiang, Wen-An; Han, Hongfang; Chen, Li-Qun; Bi, Qin-Sheng
Abstract: This paper explores a tristable energy harvesting with variational frequency by using the shape memory oscillator. The restoring force of the tristable harvester is employed via a polynomial function with variational temperature, which possess the characteristic of tristable. The effect of external temperature on natural frequency of the system is depicted. The dynamic behaviors of four different types of tristable harvesters under external harmonic and Gaussian white noise excitations are analyzed, respectively. The harvesting performances of the proposed program and the linear case are checked, the results demonstrated that tristable can be adopted to increase the steady-state bandwidth. Furthermore, the current and the power variation rules of circuit parameters are discussed. Highlights: The shape memory energy harvester has the ability to adjust the natural frequency. The qualitative behaviors of the proposed harvesters are verified by the dynamic analysis. The approximate PDF solutions are in excellent agreement with Monte Carlo results. Comparison shows that the tristability is effective than conventional linear system.